Panic buying research: A bibliometric review - Arafat, SM Yasir; Kar, Sujita Kumar; Singh, Rakesh; Menon, Vikas; Sathian, Brijesh; Kabir, Russell (Nepal Journal of Epidemiology, 2022)
Background: Panic buying has been reported during a period of crisis when people buy an extra amount of essential commodities and hoard them anticipating their future utility. As a newer entity, a bibliometric analysis would reveal the research gaps for further studies. We aimed to do a bibliometric analysis of researches published on panic buying over the past two decades. Methods: A literature search was conducted in the SCOPUS database using the keyword “panic buying”. All published research in the English language between 1st January 2001 to 1st August 2021 was included in the analysis of this study. Results: We identified a total of 142 articles on panic buying published over the past two decades. There is an exponential increase in the publication on this topic during the COVID-19 pandemic (n=127). Majority of the articles were published from the United States (n=23), followed by the United Kingdom (n=20), and China (n=20). The Frontiers in Public Health and Journal of Retailing and Consumer Services published the highest number of articles (eight each). Arafat SMY published the highest number of publications as a single author (n=10) and Enam Medical College and Hospital, Bangladesh has the highest number of papers as an institution (n=10). Among all the publishers, Elsevier has published the maximum number of papers (n=38). Conclusion: There is an exponential growth of panic buying research during 2020-21. The global crisis of the COVID-19 pandemic has been attributed to the recent rise in panic buying research.